Cardiovascular adverse events associated with BRAF versus BRAF/MEK inhibitor: Cross‐sectional and longitudinal analysis using two large national registries. (13th May 2021) - Guha, Avirup; Jain, Prantesh; Fradley, Michael G.; Lenihan, Daniel; Gutierrez, Jahir M.; Jain, Chhavi; de Lima, Marcos; Barnholtz‐Sloan, Jill S.; Oliveira, Guilherme H.; Dowlati, Afshin; Al‐Kindi, Sadeer
Abstract: Background: Cardiovascular adverse events (CVAEs) associated with BRAF inhibitors alone versus combination BRAF/MEK inhibitors are not fully understood. Methods: This study included all adult patients who received BRAF inhibitors (vemurafenib, dabrafenib, encorafenib) or combinations BRAF/MEK inhibitors (vemurafenib/cobimetinib; dabrafenib/trametinib; encorafenib/binimetinib). We utilized the cross‐sectional FDA's Adverse Events Reporting System (FAERS) and longitudinal Truven Health Analytics/IBM MarketScan database from 2011 to 2018. Various CVAEs, including arterial hypertension, heart failure (HF), and venous thromboembolism (VTE), were studied using adjusted regression techniques. Results: In FAERS, 7752 AEs were reported (40% BRAF and 60% BRAF/MEK). Median age was 60 (IQR 49–69) years with 45% females and 97% with melanoma. Among these, 567 (7.4%) were cardiovascular adverse events (mortality rate 19%). Compared with monotherapy, combination therapy was associated with increased risk for HF (reporting odds ratio [ROR] = 1.62 (CI = 1.14–2.30); p = 0.007), arterial hypertension (ROR = 1.75 (CI = 1.12–2.89); p = 0.02) and VTE (ROR = 1.80 (CI = 1.12–2.89); p = 0.02). Marketscan had 657 patients with median age of 53 years (IQR 46–60), 39.3% female, and 88.7% with melanoma. There were 26.2% CVAEs (CI: 14.8%–36%) within 6 months of medication start in those receiving combination therapy versus 16.7% CVAEs (CI: 13.1%–20.2%) among those receiving monotherapy. Combination therapy was associated with CVAEs compared to monotherapy (adjusted HR: 1.56 (CI: 1.01–2.42); p = 0.045). Conclusions and Relevance: In two independent real‐world cohorts, combination BRAF/MEK inhibitors were associated with increased CVAEs compared to monotherapy, especially HF, and hypertension. Abstract : In two independent real‐world cohorts, combination BRAF/MEK inhibitors were associated with increased cardiovascular adverse events compared to monotherapy, especially HF, and hypertension.